(3ESJQGJjLjI ebJQMI bGFei Ydi GdJbGHd GddZhi dCSJNOGe GdJQGcjH GdfMhjI ai GdcJGHI dOi GdOGQSjf GdEjWGdjjf ai GdeSJhi GdeJhSW (B= s Suggested strategy based on contrastive linguistics for using Grammar in Arabic language writing skills for Italian students at the intermediate level - (3QGfjG MeGOI eMeO eMeO YHOGdSdGes; (3EjeGf CMeO gQjOi (B: s; (3UGHQ YHOGdefYe eMeO (B: s ((3GdbGgQI (B: s (3QGfjG MeGOI eMeO eMeO YHOGdSdGe (B: s, 2020)
{u06CC}(3gOa gPG GdHMK Edi JYQa aGYd(B{u(306CC(B}(3I GdESJQGJ(B{u(306CC(B}(3L(B{u(306CC(B}(3I GdebJQMI GdbGFeI Ydi eONd GdJbGHd GddZhi dGSJNOGe GdJQGcjH GdfMhjI ai GdcJGHI dOi GdOGQSjf GdEjWGdjjf ai GdeSJhi GdeJhSW(B: (3h dJMbjb gPG GdgOa bGeJ GdHGMKI HEYOGO bGFeI HGdJQGcjH GdfMhjI GdefGSHI ddOGQSjf GdEjWGdjjf ai GdeSJhi GdeJhSW GdChd (B((3Hi(B1): (3hHfGA GNJHGQ bHdi HYOi dGSJNOGe GdJQGcjH GdfMhjI ai GdcJGHI(B: (3Ke GdJOQjS HGSJNOGe GdESJQGJ(B{u(306CC(B}(3L(B{u(306CC(B}(3I GdebJQMI GdbGFeI GdbGFeI ai cdjI GddZGJ bSe GddZI GdYQHjI HLGeYI QheG KdGKI(B. (3h bO JhUdJ GdHGMKI Edi aGYdjI GdESJQGJ(B{u(306CC(B}(3L(B{u(306CC(B}(3I GdebJQMI GdbGFeI Ydi GdJbGHd GddZhi dCSJNOGe GdJQGcjH GdfMhjI ai GdcJGHI dOi GdOGQSjf GdEjWGdjjf ai GdeSJhi GdeJhSWs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe GdefGgL h WQb GdJOQjSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJQGcjH GdfMhjIs; (3GdJbGHd GddZhis; (3GdcJGHIs